Delayed effects of a low-volume, power-type resistance exercise session on explosive performance - Tsoukos, A.; Veligekas, P.; Brown, L. E.; Terzis, G.; Bogdanis, G. C. (The Journal of Strength and Conditioning Research, 2018)
This study examined the delayed effects of a power-type training session on explosive performance. Seventeen well-trained male power and team sport athletes (age: 22.7 ± 5.5 years, height: 181 ± 8 cm, body mass: 80.7 ± 8.6 kg, body fat: 9.2 ± 1.7%, 1 repetition maximum (1RM) half-squat: 163 ± 29 kg) performed 4 sessions (2 experimental and 2 control) 1 week apart in a randomized and counterbalanced order. Explosive performance was assessed before, 24 and 48 hours after a low-volume, power-type training session (5 × 4 jump squats at 40% 1RM with 3 minutes rest), as well as before and after 24 and 48 hours of rest (control). Dependent variables were as follows: countermovement jump (CMJ), reactive strength index (RSI) during a drop jump, leg press maximum isometric force, and rate of force development (RFD) at 3 time windows: 0-100, 0-200, and 0-300 milliseconds. Analysis of variance revealed no changes in the control conditions. In contrast after training, CMJ was improved by 5.1 ± 1.0% and 3.0 ± 1.0% at 24 and 48 hours, respectively, compared with baseline. The RSI improved by 10.7 ± 2.1% only at 24 hours. The RFD increased at all time windows at 24 hours (range of improvement: 9.7 ± 3.4% to 18.3 ± 4.1%, p < 0.01). However, at 48 hours, improvement was only seen in RFD0-100 (9.8 ± 3.1%, p < 0.01). These findings suggest that a low-volume, power-type training session results in delayed enhancement of explosive muscle performance, which is greatest at 24 hours after the activity. Athletes are advised to perform power-type training 1 day before competition or a high-quality training session to improve their performances.